The effect of competence on training engagement among shooting athletes - Lee, D. W.; Kim, Y. (International Journal of Applied Sports Sciences, 2015)
This study was to examine the effect of competence on training engagement among shooting athletes. For this purpose, the data was collected from 102 participants with using Intrinsic Motivation Inventory (IMI) and training engagement scale (TES). The data was analyzed by MANOVA, correlation analysis, and multidimensional analysis. The results were as follows: Firstly, male athletes showed higher degree of cognitive and behavioral engagement than female athletes. In addition, the verification on differences in training engagement by career showed that athletes with 5 to 10 years of experience had higher degree of behavioral engagement than others. Finally, the analysis on verifying the relationship between training engagement and competence illustrated that competence was influenced by cognitive engagement. Therefore, cognitive engagement of athletes needs to be improved in order to increase the competence for shooting athletes.